2021
DOI: 10.1016/j.jhin.2020.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of SARS-CoV-2 whole genome sequencing in deciphering source of infection

Abstract: COVID-19 caused by SARS-CoV-2 is a worldwide problem. From the standpoint of hospital infection control, determining the source of infection is critical. We conducted the present study to evaluate the efficacy of using whole genome sequencing to determine the source of infection in hospitalized patients who do not have a clear infectious contact history. Recently, we encountered two seemingly separate COVID-19 clusters in a tertiary hospital. Whole viral genome sequencing distinguished the two clusters accordi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 12 publications
(15 reference statements)
2
17
0
Order By: Relevance
“…This estimation was supported by the observation that the viral genome of patient 1 remained identical to those of the locally acquired cases reported in October 2020. A similar evolutionary rate was also observed by the other studies [ 2 , 5 , 6 ]. As the interval of symptom onset between patients 1–3 and the HCWs was within one month ( Table I ), it is unlikely that the SARS-CoV-2 variant with this evolutionary rate accumulated three mutations in such short period.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…This estimation was supported by the observation that the viral genome of patient 1 remained identical to those of the locally acquired cases reported in October 2020. A similar evolutionary rate was also observed by the other studies [ 2 , 5 , 6 ]. As the interval of symptom onset between patients 1–3 and the HCWs was within one month ( Table I ), it is unlikely that the SARS-CoV-2 variant with this evolutionary rate accumulated three mutations in such short period.…”
Section: Resultssupporting
confidence: 90%
“…Novel single nucleotide polymorphism (SNP) (also known as sample-unique variants) was defined as specific nucleotide substitution in viral genome present in the corresponding sample only. A similar approach has been used to determine intra-hospital transmission of SARS-CoV-2 [ 2 , 5 ]. Multiple sequence alignment for consensus genomes was performed by Clustal Omega 1.2.0 ( http://www.clustal.org/omega/ ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The viral genetic analysis team was established by Professors of molecular biology, medical genetics, and public health to study effect of conduct molecular epidemiologic studies. 9 Research progressed at a very fast rate. Professor of the Division of Infectious Diseases and Infection Control, and Professor of the Clinical Testing Department verified a new method of serum diagnosis.…”
Section: Initiatives For Covid-19 Treatment and Researchmentioning
confidence: 99%
“…Analyses performed by the Keio Donner Project epidemiological and viral genetic analysis teams jointly formed by Department of Molecular Biology and Center for Medical Genetics also found that the cluster arising from another hospital and the cluster noted among the residents had different specific gene sequences, suggesting that they were not related to the other suspected cases of isolated occurrences and community-acquired infections. 8,9 As a result of the great efforts taken by the Division of Infectious Diseases and Infection Control, Department of Clinical Laboratory, epidemiological research team and viral genetic analysis team, along with an investigation of high-risk individuals, requests for individuals who were close contacts to self-isolate, repeated PCR testing and detailed epidemiological analysis, we were able to confirm cessation of health care-associated infections. PCR testing was performed in all 72 patients found to have fever of 37.5 °C or higher between 16th and 22nd April.…”
Section: Resolution Of Health Care-associated Infections and Further Enhancement Of Monitoring Systemmentioning
confidence: 99%